Grado de relación diámetro - altura total, según tamaño de muestra, en plantas de Guarea macrophylla M. Vahl en bosque natural, Puerto Almendra, Loreto, Perú, 2021 - Vásquez Mendoza, Miguel Ángel (2022)
The thesis was carried out at the "El Huayo" Arboretum of the Forestry Research and Teaching Center - FCF - UNAP, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine the degree of relationship between diameter - total height in the growth of Guarea macrophylla M. Vahl "requia blanca" plants in natural forest in different samples. The variables were diameter (DAP) and total height of the plants of a forest species. The results show that in the diameter-total height relationship in the Guarea macrophylla M. Vahl “requia blanca” plants, the potential allometric model was defined as the one that best adjusted to the data of the evaluated relationship; Likewise, the degree of relationship was excellent. For predictions of the diameter-total height relationship, the power equation will be applied.